Long-Term Evaluation of Changes in Kidney Function after Switching from Tenofovir Disoproxil Fumarate to Tenofovir Alafenamide in Patients Living with HIV - Jared M. Gilbert; Kirsten Vest; Troy D. Kish (MDPI AG, 2022)
Tenofovir is one of the most widely used medications for HIV treatment and is administered as either tenofovir disoproxil fumarate (TDF) or tenofovir alafenamide (TAF). Use of TAF is preferred as it is associated with fewer negative impacts on renal function; however, long-term follow-up beyond 96 weeks is limited. A retrospective chart review of patients ≥18 years who received TDF-containing anti-retroviral therapy (ART) for ≥6 months and then switched to a TAF-containing regimen between 1 December 2015 and 1 January 2020 is presented. The primary objective was to evaluate changes in kidney function as measured by eGFR and Scr. The secondary objective was to evaluate changes in lipids. Among the 142 patients identified, the median age was 66 years old with a median follow-up of 3.6 years. The change in kidney function was a median increase in Scr of 0.1 mg/dL and a decrease in eGFR of −8 mL/min/1.73 m2. The change in lipid panels at the end of the medication use evaluation endpoint was a decrease in total cholesterol, LDL, HDL, and triglycerides of −2.5, −0.1, −0.6, and −9 mmol/L, respectively. There was no clinically meaningful difference in kidney function as measured by eGFR or Scr, nor was there any clinically meaningful difference in lipid panels in patients switched from TDF to TAF-containing ART. Our observations suggest that the favorable impact of TAF on kidney function is sustained for at least 44 months after conversion from TDF.